IMMOBILIZATION STRESS INFLUENCE ON LEUKOPOIESIS INDEX AND ON ACTIVITY CHANGES OF PROLINE BIOSYNTHESIS ENZYMES (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
In the article immobilization stress influence on leukopoiesis index, as well as on activity changes of proline biosynthesis enzymes on rabbit are studied. At the first stages of immobilization stress action increase of quantities of left bent neutrophilose nucleus and lymphocytes was observed, due to their quick access from bone marrow to peripheral blood: granulocytes bone marrow reserve, granulocytes bone marrow reserve, spleen and thymus lymphocytic cells stressor mobilization. Neutrophenia, eosynophenia and basophenia were also observed, during immobilization stress action duration increasing. Young and mature neutrophils quantity decrease has been observed in myelogram, that is the consequence of pressure proliferative and maturation processes of leukoblastic spire. Тhe highest enzyme activity in natural conditions was registered in liver and adrenal glands, whereas in conditions of immobilization stress the enzymes’ activities were changed and were detected in rabbit brain.
Keywords: immobilization stress, leukopoies, ornithine transaminase, proline-5-carboxylase reductase